Analysis of risk variables for association with maxillary sinus mucosal thickenings: a cone‑beam computed tomography‑based retrospective study (2023)
Purpose This study aimed to determine which patient-related, anatomical, pathologic, or iatrogenic variables may be directly associated with and which may have a modifying efect on the generation of maxillary sinus (MS) mucosal thickenings. Methods A total of 278 cone-beam computed tomography (CBCT) scans obtained from 114 males and 164 females were evaluated. The protocol included the assessment of 21 candidate variables, of which 18 were bilateral and 3 were unique. The relationship among the study variables and the mucosal thickenings were examined individually and adjusted for confounding using univariate and multivariate binary logistic regression models. Results The prevalence of mucosal thickenings was 71.20% at patient level and 53.40% at sinus level. The ostium height>28.15 mm, the infundibulum length≤9.55 mm, the infundibulum width≤0.50 mm, along the occurrence of periapical lesions and slight-to-severe periodontal bone loss acted as strong/independent risk variables for MS mucosal thickenings. Confounding and interaction relationships between MS height and depth, and between the alveolar process type and the presence of foreign materials with respect to age stratum>47.50 years might be also associated with the mucosal thickenings. Conclusions While increased ostium height, decreased infundibulum length/width, the presence of periapical lesions and periodontal involvement might be the foremost indicator variables for MS mucosal thickenings, there are synergistic relationships among the increased sinus height and depth as well as aging regarding atrophic/partially atrophic alveolar process status and the presence of foreign materials that may be also associated with a greater proportion of these mucosal abnormalities.